Navigating Fragility and Building Resilience: A School–University Partnership to Support the Development of a Full-Service Community School. Issue 12 (November 2019) - Herrenkohl, Leslie Rupert; Napolitan, Kate; Herrenkohl, Todd I.; Kazemi, Elham; McAuley, Logan; Phelps, David
Background/Context: The literature review by Phelps in this special issue highlights the challenges of research–practice partnerships and other forms of insider–outsider collaboration in education. In addition to addressing well-known challenges, this case study article focuses on the full-service community school model as a strategy to address holistic needs of students, families, and staff in poverty-impacted school contexts. Purpose/Objective/Research Question/Focus of Study: This article documents work that was conducted across five years, when a large research university partnered with an urban elementary school to establish a full-service community school. It provides an account of the assets, challenges, and processes that impacted our work, from the planning phase through four years of implementation. It describes efforts around four main areas: academic excellence, extended learning, holistic health and wellness, and family engagement. Research Design: This is a participatory case study with university educators and researchers working collaboratively with school professionals, community-based organizations, and families. Data Collection and Analysis: Many sources of data were included in our case analysis, including formative and summative student assessments, student attendance, service referrals, and office referrals for behavior. Running records of meetings, documentation of events, presentations, and reports submitted were also included. Interviews with key actors in the project were also collected and analyzed. Conclusions/Recommendations: Our partnership experienced some of the major challenges discussed in the literature. Turnover was overwhelmingly the most significant challenge. Student mobility and district boundary changes, new curricular adoptions for mathematics and literacy, new student assessments, new data tracking system, new bell times, and measures to cut transportation costs also impacted the effort. In spite of these challenges, we also experienced important successes. Centering relationships in our work has been an essential part of the success we experienced and is itself a success. At every phase, we remained at the table together, working to build relationships and sharing visions, goals, and practices. This resulted in important changes with stronger systems for tracking and using student data in educational decision making, health and wellness services now available to all students, and a universal social-emotional curriculum now in place. Family engagement and parent leadership are now essential dimensions of the school, with parents of color playing important roles to amplify their own and other parents' voices. Preservice teachers learned about full-service community schools in situ. We highlight the rich and complex narrative that emerged, which is not simply one of challenge but also one of resilience and strength. Carefully documenting this initiative can contribute to guiding implementation and refinement of a full-service community school model.